Identification of a novel psoriasis susceptibility locus at 1p and evidence of epistasis between PSORS1 and candidate loci. Issue 1 (1st January 2001) - Veal, C D; Clough, R L; Barber, R C; Mason, S; Tillman, D; Ferry, B; Jones, A B; Ameen, M; Balendran, N; Powis, S H; Burden, A D; Barker, J N W N; et al.
Abstract : The pathogenesis of all forms of psoriasis remains obscure. Segregation analysis and twin studies together with ethnic differences in disease frequency all point to an underlying genetic susceptibility to psoriasis, which is both complex and likely to reflect the action of a number of genes. We performed a genome wide analysis using a total of 271 polymorphic autosomal markers on 284 sib relative pairs identified within 158 independent families. We detected evidence for linkage at 6p21 ( PSORS1 ) with a non-parametric linkage score (NPL)=4.7, p=2 × 10 -6 and at chromosome 1p (NPL=3.6, p=1.9 × 10 -4 ) in all families studied. Significant excess (p=0.004) paternal allele sharing was detected for markers spanning the PSORS1 locus. A further three regions reached NPL scores of 2 or greater, including a region at chromosome 7 (NPL 2.1), for which linkage for a number of autoimmune disorders has been reported. Partitioning of the data set according to allele sharing at 6p21 ( PSORS1 ) favoured linkage to chromosomes 2p (NPL 2.09) and 14q (NPL 2.0), both regions implicated in previous independent genome scans, and suggests evidence for epistasis between PSORS1 and genes at other genomic locations. This study has provided linkage evidence in favour of a novel susceptibility locus for psoriasis and provides evidence of the complex mechanisms underlying the genetic predisposition to this common skin disease.